Literary and Philosophical Essays: French, German and Italian - Montaigne, Michel de, 1533-1592; Kant, Immanuel, 1724-1804; Lessing, Gotthold Ephraim, 1729-1781; Mazzini, Giuseppe, 1805-1872; Renan, Ernest, 1823-1892; Sainte-Beuve, Charles Augustin, 1804-1869; Schiller, Friedrich, 1759-1805 (Salt Lake City, UT : Project Gutenberg, 2004)
"Literary and Philosophical Essays: French, German and Italian" by Montaigne et al. is a collection of essays and philosophical reflections likely written during the late 16th century. The work features profound insights into various aspects of human experience, including happiness, education, friendship, and the nature of philosophy itself. Montaigne's essays are characterized by their introspective quality and blend of personal narrative with broader philosophical inquiry. The opening of the collection introduces Michel de Montaigne, establishing his historical context and emphasizing his role as a pioneer of the essay form. Montaigne reflects on the uncertainty of happiness, arguing that true judgements cannot be made until after one's death. He draws on historical examples and philosophical teachings to illustrate his points, particularly emphasizing the importance of understanding death as a pivotal aspect of life. Moreover, he presents self-awareness and introspection as crucial tools for navigating life's complexities, setting the tone for the essays that follow, which promise a mixture of personal revelation and philosophical discourse. (This is an automatically generated summary.)
That we should not judge of our happiness until after our death. That to philosophise is to learne how to die. Of the institution and education of children. Of friendship. Of bookes. By Montaigne -- Montaigne. What is a classic? By C. A. Sainte-Beuve -- The poetry of the Celtic races, by E. Renan -- The education of the human race, by G. E. Lessing -- Letters upon the aesthetic education of man, by J. C. F. von Schiller -- Fundamental principles of the metaphysic of morals. Transition from popular moral philosophy to the metaphysic of morals. By I. Kant -- Byron and Goethe, By B. Mazzini
Release date is 2004-05-01
David Turner, Charles Franks and the Online Distributed Proofreading Team
Keywords: Essays